Cement-Stabilized Granular Volcanic Ash Materials for Construction of Low-Traffic Roads in Yemen - Alhadama, Saddam H.; Almaswari, Abdullah A.; Algaboby, Ziyad M. (Wiley, 2024)
Granular volcanic ash (GVA) is a volcanic activity material with low density, high porosity, and other undesirable properties that must be improved prior to use in any construction. This material can be considered an alternative for use in road building, given its availability in many locations and in large quantities in Yemen. This article aims to investigate the potential use of GVA for the construction of roads in Yemen when treated with cement stabilizer. Two types of GVA materials with different colors were selected and referred to as red and black GVA materials. Tests performed included the unconfined compressive strength (UCS), compaction, indirect tensile strength (ITS), wetting-drying durability test, and ultrasonic pulse velocity (UPV) test for samples curried for 7 and 28 days. For each GVA-cement mixture, the cement content varied as 2%, 5%, and 8% by dry weight of GVA. Test results revealed that the compaction energy applied during sample preparation led to a significant reduction in the finesse modulus for red and black coarse GVA materials, with reductions of 10% and 23%, respectively. In addition, the cement content and curing period had a significant effect on UCS, ITS, and UPV for cement-treated GVA. The applicable quantity of cement required stabilizing GVA and achieving the base course specification for strength and durability criteria in flexible pavement with low traffic is 8% cement.